In-plane flexible ring modeling and a nonlinear stiffness solution for heavy-load radial tires. (15th May 2022) - Liu, Zhihao; Liu, Yixun; Gao, Qinhe
Highlight: Flexible ring on the two-dimensional elastic foundation; updated analytical stiffness of the curved sidewall beam; grounding contact with with the interative numerative method. Abstract: This paper presents a complete tire model for heavy-load radial tires with a large section ratio that is based on a flexible carcass ring model, combined with a sidewall element with two-dimensional stiffness. It also establishes a two-dimensional analytical model of sidewall stiffness for heavy-duty tires based on preloaded beam deformation theory. The flexible ring model is used to examine the ground-contact modeling of heavy load tires and their stiffness characteristics are analyzed. Experimental and theoretical results show that flexible ring tire models based on nonlinear elastic foundations can accurately characterize the grounding mark of tires and their stiffness characteristics, with there being a good fit between the theoretical and experimental results. The analytic two-dimensional function for curved sidewalls developed in the paper can also be used to enrich other tire models, such as FTire and CDTire.